USING INTERACTIVE METHODS TO DEVELOP STUDENTS’ READING SKILLS IN ENGLISH - Eshmuratov Muzaffar Elamonovich (Bright Mind Publishing, 2025)
This article analyzes the effectiveness of using interactive methods in developing students’ reading skills during the process of teaching English. It highlights the role of communicative, motivational, and technological approaches in fostering reading competence and provides practice-based recommendations. Observation, survey, and experimental methods were applied in the study, and the effectiveness of such methods as interactive games, clustering, “brainstorming,” “Padlet,” and “Kahoot” was determined.
Keywords: Interactive methods, reading skill, communicative competence, English language, student, learning process.